Estimating the prevalence, clinical characteristics, and treatment patterns of hypertrophic cardiomyopathy in Japan: A nationwide medical claims database study. Issue 3 (March 2023) - Terasaka, Naoki; Spanopoulos, Dionysis; Miyagoshi, Hidetaka; Kubo, Toru; Kitaoka, Hiroaki
Abstract: Background: Limited data are available regarding therapies for hypertrophic cardiomyopathy (HCM). This study assessed the prevalence, clinical characteristics, and treatment patterns of HCM in Japan. Methods: This retrospective database study analyzed data from 438 hospitals in the Japan Medical Data Vision database from 2016 to 2020. We identified 3913 patients (15 %) with obstructive HCM (oHCM) and 21, 714 patients (85 %) with nonobstructive HCM (nHCM). Results: The estimated total number of patients with oHCM and nHCM in 2020 among Japanese hospitals was 8500 and 43, 500, respectively. The prevalence of oHCM and nHCM steadily increased by 27 % and 12 %, respectively, from 2016 to 2020, with a 1:5.2 ratio of oHCM to nHCM in 2020. The mean age of the oHCM and nHCM populations was 72 and 70 years, respectively, and comorbidities included atrial fibrillation (AF) (oHCM, 33.8 %; nHCM, 32.2 %), other arrythmia (30.1 %; 27.6 %), and stroke (16.6 %; 16.4 %). Furthermore, 45.0 % of oHCM and 37.7 % of nHCM patients had undergone at least one hospitalization. A substantial number of HCM patients aged between 20 and 59 years reported AF (oHCM, 17–37 %; nHCM, 4–24 %) and stroke (oHCM, 0–12 %; nHCM, 3–10 %). β-blockers (oHCM, 64.0 %; nHCM, 42.1 %) were the most frequently prescribed treatment, followed by Na channel blockers (29.5 %; 5.7 %), calcium channel blockers (18.1 %; 8.8 %), direct oral anticoagulants (14.5 %; 15.2 %), and warfarin (11.0 %; 11.4 %). Conclusions: This study provides important information on the current epidemiological and clinical characteristics of HCM in Japan. Graphical abstract: Unlabelled Image Highlights: Patients with hypertrophic cardiomyopathy in Japan have increased 2-fold since 1999. The ratio of obstructive and nonobstructive hypertrophic cardiomyopathy was 1:5.2. The prevalence of atrial fibrillation was 32–33 %. Around 16 % of patients experienced stroke. Substantial numbers of patient <40-years-old had atrial fibrillation and stroke.